An Analysis of The Determinants of Financial Distress in The Operations of Mining Companies in Indonesia, with Export Dependence as a Moderating Variable - Andrie Wiyogo; Choirul Anwar; Etty Gurendrawati (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This study examines the determinants of financial distress in mining companies listed on the Indonesia Stock Exchange (IDX), with export dependence as a moderating variable. The research focuses on internal financial factors including liquidity, leverage, profitability, and firm growth as well as firm size as a control variable, to explain variations in financial distress. In addition, export dependence on major trading partners is introduced to assess its moderating role in strengthening or weakening the relationship between profitability and financial distress. A quantitative approach is employed using secondary data from annual financial reports of 22 mining companies over the 2021–2024 period, yielding 88 firm-year observations. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) via SmartPLS software. The results indicate that liquidity has a significant positive effect on financial distress, while leverage has a significant negative effect. Profitability shows a significant positive relationship with financial distress, whereas firm growth has no significant effect. Export dependence significantly moderates the relationship between profitability and financial distress, strengthening the impact of profitability on financial stability. Meanwhile, firm size does not significantly influence financial distress. The study concludes that financial distress in mining companies is primarily driven by internal financial performance, while external dependency on export markets plays a critical moderating role. These findings highlight the importance of financial resilience and export market structure in mitigating corporate financial risk.